Biofidelity evaluation of WorldSID and ES-2re under side impact conditions with and without airbag. (May 2016) - Kim, Taewung; Shaw, Greg; Lessley, David; Park, Gwansik; Crandall, Jeff; Svendsen, Andy; Whitcomb, Bryant; Ayyagari, Murthy; Mishra, Prashast; Markusic, Craig
Highlights: The response of WorldSID was closer to that of the PMHS than the ES-2re under whole-body side impact conditions with and without an airbag. The WorldSID demonstrated better whole-body kinematics due to its compliant lumbar spine region. The ES-2re missed a load path between the impacting wall and its thorax due to its stiff lumbar spine and excessive arm rotation. The shoulder of the WorldSID was overly compliant in the condition with no airbag, suggesting the need for modification at this level of impact severity. Abstract: This study evaluated the biofidelity of the WorldSID and the ES-2re under whole-body side impact conditions with and without a side airbag using the biomechanical cadaveric response data generated from 4.3 m/s whole-body side impact tests. Impact forces, spinal kinematics, and chest deflections were considered in the biofidelity evaluation. Average responses and response corridors of PMHS were created using a time-alignment technique to reduce variability of the PMHS responses while maintaining the sum of the time shifts to be zero for each response. Biofidelity of the two dummies was compared using a correlation and analysis (CORA) method. The WorldSID demonstrated better biofidelity than the ES-2re in terms of CORA ratings in the conditions with airbag (0.53 vs. 0.46) and without an airbag (0.57 vs. 0.49). Lastly, the kinematic analysis of the two dummies indicated an overly compliant shoulder response of the WorldSID and excessive forward rotation of the ES-2re relative to the PMHS.